The Engineered Antibiotic Peptide PLG0206 Eliminates Biofilms and Is a Potential Treatment for Periprosthetic Joint Infections - David Huang; Nicholas Pachuda; John Michael Sauer; Dessie Dobbins; Jonathan Steckbeck (MDPI AG, 2021)
Antimicrobial peptides (AMPs) have recently gained attention for their potential to treat diseases related to bacterial and viral infections, as many traditional antimicrobial drugs have reduced efficacy in treating these infections due to the increased prevalence of drug-resistant pathogens. PLG0206, an engineered cationic antibiotic peptide that is 24 residues long, has been designed to address some limitations of other natural AMPs, such as toxicity and limited activity due to pH and ion concentrations. Nonclinical studies have shown that PLG0206 is highly selective for targeting bacterial cells and is not toxic to human blood cells. Antibiofilm experiments demonstrated that PLG0206 is effective at reducing both biotic and abiotic biofilm burdens following direct biofilm contact. PLG0206 has rapid and broad-spectrum activity against both Gram-positive and Gram-negative bacteria that are implicated as etiologic agents in periprosthetic joint infections, including multidrug-resistant ESKAPE pathogens and colistin-resistant isolates. A recent first-in-human study demonstrated that PLG0206 is well tolerated and safe as an intravenous infusion in healthy volunteers. Studies are planned to determine the efficacy of PLG0206 in patients for the treatment of periprosthetic joint infections. This review summarizes the chemistry, pharmacology, and microbiology of PLG0206 and explores its current preclinical, clinical, and regulatory status.